Announcing Automated Lane Changes: Active Vehicle Roll Motions as Feedback for the Driver. Issue 11 (3rd July 2019) - Cramer, Stephanie; Klohr, Jana
ABSTRACT: As supervisor of the automation system during partially automated driving, it is essential for the driver to have a good awareness of the automation to fulfill this new task sufficiently. Therefore, feedback about intentions of the automation, for example lane changes, is crucial. So far, this feedback is mainly presented visually to the driver. Conversely, in this article, feedback for announcing lane changes is realized via active vehicle roll motions. Several designs are implemented in an automated test vehicle and are evaluated in four different driving scenarios on a test track. Totally, 39 participants rated the vehicle roll motions, for example, regarding the items roll direction, intensity, usefulness, and the predictability of the driving behavior. The results show that active roll motions as feedback for announcing automated lane changes should be clearly perceptible and are considered useful, not misleading, and support the drivers regarding their mode/system awareness.